Design and Development of an ESP32-Based Internet of Things Smart Farming System for Monitoring and Automatic Aeration in Tubifex sp. Cultivation: Rancang Bangun Sistem Smart Farming Berbasis Internet of Things Menggunakan ESP32 untuk Monitoring dan Aerasi Otomatis pada Budidaya Cacing Sutera - Muhamad Ludpi; Raimon Efendi; Efri Yandani (Journal of Vocational Education and Information Technology (JVEIT), 2026)
Tubifex (Tubifex sp.) cultivation requires optimal water quality management because environmental parameters, such as temperature and pH, directly affect growth and productivity. Conventional water quality monitoring is generally performed manually, resulting in delayed detection of environmental changes that may reduce cultivation performance. This study aimed to develop an Internet of Things (IoT)-based smart farming system using an ESP32 microcontroller for real-time water quality monitoring and automatic aeration control. The study employed a Research and Development (R&D) approach consisting of needs identification, system design, implementation, testing, and evaluation. The proposed system integrates a DS18B20 temperature sensor, a pH sensor, an ESP32 microcontroller, a relay module, an aerator, and the Blynk platform for remote monitoring. Sensor data are transmitted to the Blynk application via the Internet, enabling real-time visualization of water quality parameters, while the aerator is automatically activated based on predefined temperature and pH threshold values. Experimental results demonstrated that the system successfully monitored temperature and pH in real time, displayed sensor data accurately on the Blynk platform, and automatically controlled aeration when water quality parameters exceeded the optimal range. The developed system improves monitoring efficiency, enables rapid responses to water quality fluctuations, and supports more effective and sustainable management of Tubifex cultivation.